Knowledge of Basic Accounting Issues of SBA Students and their View on the Qualification Level of Professional Accountants - Markéta Šeligová; Ivana Koštuříková (European Financial and Accounting Journal, 2021)
The aim of the article is to evaluate the level of basic knowledge of accounting issues of students of the School of Business Administration in Karviná (SBA) in the Czech Republic and verify the existence of dependence of their knowledge on gender, secondary education, aspects of their university studies, and last but not least, on their work experience. Furthermore, the research aims to find out how these students perceive the importance of the qualification level of professional accountants. In order to achieve the objective of the article, a questionnaire survey was used. On the basis of the acquired nominal data, the non-parametric Kruskal-Wallis test was used to answer the first research question concerning the impact of aspects of the university study on the level of student accounting knowledge. As part of the research, 1,035 students were contacted and 709 respondents have completed the questionnaire. The perceptions of the accountant profession were examined using the Pearson's chi-square test and the Pearson's coefficient of contingency. It can be concluded from the results that the form of study and the degree of study have no influence on the level of students' knowledge. In the field of study, on the other hand, the dependence of accounting knowledge of students on this aspect has already been proved. The work experience of students was most markedly reflected in the students' accounting knowledge.
Keywords: A10; I21; M41; 650; Accountant profession; Accounting; education; Kruskal-Wallis test; Pearson Chi-square test; Pearson coefficient; University studies; Work experience